Analysis Of Work Motivation At Ria Busana Sumedang - Ismiyanti, Iis Salamah; Henriawan, Desan; Kartika, Tita (Journal of Bussines Management Basic, 2025)
This research focuses on work motivation at Ria Busana Sumedang. The purpose of this research is to find out how work motivation at Ria Busana Sumedang. How are efforts to increase work motivation at Ria Busana Sumedang. The method used in this research is a qualitative approach. In this study using two data collection techniques, namely by means of observation and interviews. The informants of this study were 15 people consisting of Sales Executive, and Sales Assistant. Data analysis researchers use Milles and Hubarman mode analysis method, activities in data analysis are data reduction, data display, and conlusion drawing / verification. Based on the results of interviews, observations and data analysis, it is concluded that work motivation at Ria Busna Sumedang is quite good in terms of physiological needs, security needs, appreciation needs, and self-actualization needs. Efforts to increase employee motivation at Ria Busana Sumedang are physiological needs by providing salaries, bonuses, and adequate facilities for employees to work. Security needs, namely the security of a safe work environment, and fair treatment. Social needs, namely good communication, mutual respect, good and compact relationships and cooperation. Award needs, the company gives awards to employees, gives appreciation, and praise to outstanding employees. Self-actualization needs, the company provides freedom to develop talents and expertise for employees, and can accept each other’s opinions.